2007
DOI: 10.1590/s1516-635x2007000200004
|View full text |Cite
|
Sign up to set email alerts
|

On the use of a probiotic (Bacillus subtilis - strain DSM 17299) as growth promoter in broiler diets

Abstract: The objective of this experiment was to evaluate the effect of a probiotic (Bacillus subtilis, strain DSM 17299) in broiler diets on feed intake, weight gain, and feed conversion ratio. The experiment included 1,200 male Ross broilers from 1 to 42 days of age. Birds were randomly allocated to 4 treatments, with 10 replicates of 30 birds. The following treatments were applied: T1 - Negative Control (basal diet, with no added growth promoter; T2 - Negative Control + Bacillus subtilis (8 x 10(5) CFUs/g feed); T3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
2
9
1
3
Order By: Relevance
“…This result was in agreement with outcomes of Zhang and Kim (2014), Amerah et al (2013), Toghyani et al (2011), andOpalinski et al (2007). Amerah et al (2013) reported that probiotic supplementation reduced FI and improved FCR with no effect on weight gain throughout the trial, indicating that the probiotic indeed exerted some beneficial effect on broilers.…”
Section: Resultssupporting
confidence: 88%
“…This result was in agreement with outcomes of Zhang and Kim (2014), Amerah et al (2013), Toghyani et al (2011), andOpalinski et al (2007). Amerah et al (2013) reported that probiotic supplementation reduced FI and improved FCR with no effect on weight gain throughout the trial, indicating that the probiotic indeed exerted some beneficial effect on broilers.…”
Section: Resultssupporting
confidence: 88%
“…These results were partly different from those found by Brito et al (2005), Opalinski et al (2007) and Meurer et al (2010), who observed better performance in broilers fed both diets supplemented with the additives (AGP or BS) alone and combined. Rigobelo et al (2008) found better feed conversion in broilers fed probiotic or AGP-supplemented diets when compared with the broilers in the negative control group.…”
Section: Resultscontrasting
confidence: 99%
“…on bird's performance in case of absence of enteric infections revealed that these compounds are effective as they improve the growth of the broiler chickens (Mohan et al, 1996;Jin et al, 1998;Zulkifli et al, 2000;Kalvathy et al, 2003;Gracia et al, 2004;Huang et al, 2004;Opalinski et al, 2007;Midilli et al, 2009). On the other hand, Angle et al, (2005) found no improvement in performance but there were increased protein, calcium and phosphorus retention.…”
Section: Contrary Results Were Mentioned Bymentioning
confidence: 99%